Developing a sprayable drug delivery system for the local delivery of nanoparticles in glioblastoma multiforme - McCrorie, Phoebe (2021)
Glioblastoma multiforme (GBM) is a World Health Organisation classified grade 4 tumour with a dismal median survival time of 14 months from diagnosis and a 16% 2-year survival rate. Current treatment consists of debulking surgery followed by concurrent radiotherapy and temozolomide chemotherapy. Relapse from residual disease cells is inevitable, with 80% of tumours recurring within 2 cm of the primary tumour resective margin. This gives high precedence for a local drug delivery system (DDS) to target residual disease within neighbouring brain parenchyma. A spray device and formulation (polymer-coated nanoparticles (PCNPs) and hydrogel) has been developed to achieve further penetration of drug into this 2 cm target area.